2016
DOI: 10.1080/00028487.2016.1152299
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Predation on Early Life Stage Delta Smelt in the San Francisco Estuary Using DNA Diet Analysis

Abstract: We examined predation by nonnative Mississippi Silversides Menidia audens, other small fishes, and invertebrates on the early life stages of the endangered Delta Smelt Hypomesus transpacificus, which is endemic to the Sacramento–San Joaquin Delta in California. Mississippi Silversides and other putative predators were collected primarily via boat electrofishing in the northern reaches of the upper San Francisco Estuary, an area targeted for substantial tidal wetland restoration to enhance habitat for Delta Sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Testable study ques- Mahardja, Conrad, Lusher, & Schreier, 2016;Schreier, Baerwald, Conrad, Schumer, & May, 2016) and may compete for similar resources; therefore, Mississippi silversides are likely to be susceptible to similar predation pressures as delta smelt. Testable study ques- Mahardja, Conrad, Lusher, & Schreier, 2016;Schreier, Baerwald, Conrad, Schumer, & May, 2016) and may compete for similar resources; therefore, Mississippi silversides are likely to be susceptible to similar predation pressures as delta smelt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testable study ques- Mahardja, Conrad, Lusher, & Schreier, 2016;Schreier, Baerwald, Conrad, Schumer, & May, 2016) and may compete for similar resources; therefore, Mississippi silversides are likely to be susceptible to similar predation pressures as delta smelt. Testable study ques- Mahardja, Conrad, Lusher, & Schreier, 2016;Schreier, Baerwald, Conrad, Schumer, & May, 2016) and may compete for similar resources; therefore, Mississippi silversides are likely to be susceptible to similar predation pressures as delta smelt.…”
Section: Introductionmentioning
confidence: 99%
“…The overall goal of this study was to characterise individual and group movement behaviour of delta smelt and determine if high temperature increases predation vulnerability. Testable study ques- Mahardja, Conrad, Lusher, & Schreier, 2016;Schreier, Baerwald, Conrad, Schumer, & May, 2016) and may compete for similar resources; therefore, Mississippi silversides are likely to be susceptible to similar predation pressures as delta smelt. The present study tested chronic and acute exposures to 21°C, a moderate thermal challenge well within tolerance limits (Davis et al, 2019;Jeffries et al, 2016;Komoroske et al, 2014) of fishes that will provide relevant information to current and future habitat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mississippi Silversides Menidia beryllina prey upon Delta Smelt larvae (Schreier et al. ) and have increased greatly in abundance in shallow waters (Bennett ), but they are not quantitatively sampled by any monitoring program. The most likely predators on juvenile and adult Delta Smelt are Striped Bass (Nobriga et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, information is lacking on fine-scale population densities and feeding rates of likely predators of Delta Smelt (Nobriga et al 2013). For example, Mississippi Silversides Menidia beryllina prey upon Delta Smelt larvae (Schreier et al 2016) and have increased greatly in abundance in shallow waters (Bennett 2005), but they are not quantitatively sampled by any monitoring program. The most likely predators on juvenile and adult Delta Smelt are Striped Bass (Nobriga et al 2013) and Largemouth Bass Micropterus salmoides.…”
Section: What Is Not In the Model?mentioning
confidence: 99%
“…Striped Bass diet studies have revealed that very few smelt are eaten, although DNA techniques have identified Delta Smelt DNA in the stomachs of many species, including Striped Bass (Baerwald et al 2012;Schreier et al 2016). Predation by large predators does not (Grossman 2016).…”
Section: Predator Removalmentioning
confidence: 99%